ErIK—a software-based identification key for earthworm species of Croatia - Hackenberger, Davorka K.; Hackenberger, Domagoj K.; Đerđ, Tamara; Hackenberger, Branimir K. (Zootaxa, 2019)
The need for reliable taxonomic species identification is always present. Correct identification of specimens is based on taxonomic research, scattered in the scientific literature and accessible only for a restricted group of specialists or research institutions with extensive library facilities (Zuquim et al. 2017). Therefore, identification keys that summarize the knowledge of a group of biota are very important; they provide the link between producers and users of taxonomy. Recently, printed identification keys are increasingly being replaced or supplemented by computer-aided keys.